Sexual Interest in Children Among Women in Two Nonclinical and Nonrepresentative Online Samples. Issue 2 (4th March 2020) - Tozdan, Safiye; Dekker, Arne; Neutze, Janina; Santtila, Pekka; Briken, Peer
Abstract: Introduction: Regarding women, little research is available about the prevalence of sexual interest in children (SIC), especially in nonclinical samples. Aim: The present study aimed to investigate the extent to which adult women from 2 nonclinical and nonrepresentative samples indicate sexual interest in prepubescent and/or pubescent children. Methods: Participants took part in an online survey either via general websites or via websites directed toward individuals with a SIC. Main Outcome Measures: The self-report survey included questions about the use of online abuse material including children and teenagers as well as about sexual fantasies involving prepubescent and pubescent children. Both measures were included as main outcome measures. Results: Results showed that few women reported having used online abuse material including children (total sample: n = 7 [0.8%], general websites: n = 3 [0.4%], SIC websites: n = 4 [9.5%]) or teenagers (total sample: n = 44 [5.0%], general websites: n = 37 [4.4%], SIC websites: n = 7 [16.7%]). Results further revealed that some women reported sexual fantasies involving prepubescent (total sample: n = 98 [7.0%], general websites: n = 92 [6.8%], SIC websites: n = 6 [11.1%]) or pubescent children (total sample: n = 136 [9.6%], general websites: n = 129 [9.5%], SIC websites: n = 7 [13.0%]). Conclusions: The samples included are nonrepresentative and therefore not generalizable to the female population. Nevertheless, they strongly suggest that SIC is a phenomenon also found in women. We therefore recommend professionals in the field of sexual medicine to increase their attention and engagement for women with SIC. Based on the present results, the development of preventive treatment services specifically tailored to women with a SIC has to be strongly encouraged in the near future. Tozdan S, Dekker A, Neutze J, et al. Sexual Interest in Children Among Women in Two Nonclinical and Nonrepresentative Online Samples. Sex Med 2020;8:251–264.